The Effect of Authentic Materials on Students’ Reading Comprehension of Short Functional Text - Akhmad Nuris Hidayat (PPPM STIT MIFTAHUL MIDAD, 2022)
Authentic materials and Textbook are the materials which affect reading comprehension. The purpose of this research is to find out whether there is any significant gap of students' reading comprehension of short functional text who are taught using authentic materials and textbook at first grades of SMA Diponegoro Panti Jember. 70 students are taken from first grades of SMA Diponegoro Panti Jember (X IPS 1 and X IPS 2), which are an experimental class (35 students) and a control class (35 students) for research sample. The design in this research is a quasi-experimental design. In collecting the data, the researcher conducts pre-test and post-test by serving the reading comprehension test which consist of 20 multiple choice items for each test. In analyzing the data, the researcher uses a T-Test. The result of this research shows that there is a significant gap in students' comprehension of short functional text by using authentic material than the textbook. In the table of significance, it can be seen that on the df = 68 and in the degree of significance 5% the value of the degree of significance is 1.66. By comparing the value to is bigger than tt. The result shows that t-test (to) > t-table (tt) (2.11 >1.66). The alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected.